Pembangunan Hukum Sebagai Upaya Peningkatan Daya Saing Daerah - Rahayu, Dewi Ayu (University of Merdeka Malang, 2019)
Implementation, development is not a stand-alone entity, but rather integrated and becomes a unit with existing development components. The purpose of this study is to examine legal concepts through legal development as an effort to realize regional competitiveness. The type of research that will be used is Juridical-Normative Researchers. This research in conjunction with the juridical-normative method in this study uses the results of this study to show that regional competitiveness correlates with the development of national law as stated in Law Number 17 of 2007 concerning the National Long- Term Development Plan that was previously listed in the Outlines of State Policy. The second generation legal theory of development through legal concepts is not only a means of development, but also as a means of renewing the bureaucracy. The development of laws that will improve the competitiveness of the nation needs to pay attention to three important things, first, the development of quality and beneficial legislation. Realizing the competitiveness of each region in Indonesia, which of course will have an impact on the welfare of the State, of course, must be accompanied by legal development both in the substance of the law, legal structure and legal culture.How to cite item:Â Rahayu, D. (2019). Pembangunan Hukum Sebagai Upaya Peningkatan Daya Saing Daerah.Â Jurnal Cakrawala Hukum, 10(1), 1-8. doi:https://doi.org/10.26905/idjch.v10i1.3181